Corrective collegiality, precedents and cognitive biases: some CPC-2015 issues (Revista do Tribunal Regional Federal da 3ª Região, 2016)
This essay discusses the collegiality as reviewing guarantee (correction) of decisions and it’s relation with precedents and cognitive biases (judgment incorrections), always from the of principles brought by the CPC-2015. The discussion takes place upon presentation of the problem on the effective possibility of review of decisions collectively; of regulations relating to precedents in the new Code; the need to draw up a useful report about each cause under review (formation of determinants pleas); the relation between the collegiality and the numerous factors that influence and distort the form of judgment from judges, for example, the confirmation bias; the celebrated regulation of the possibility of modifying the votes of the judges during the trial upon the facts stated in session; and; the collegiate expansion incident to the resolution of non-unanimous decisions (art. 942 CPC-2015). It’s concluded from this study that the new decision-making assumptions contained in CPC-2015 are scoped in the search for a genuine and satisfactory debate to increase the fairness of decisions, forming extractable skilled decisive foundations for the implementation of the precedents system as legitimate possibility for discussion of law. Collegiality seems as collateral linked to the dynamic contradictory, primary objective of the democratic constitutional processualism.
Keywords: collegiality; cognitive biases; precedents; dynamic contradictory; democratic constitutional